Sleep Quality, Body Mass Index and Waist-to-Hip Ratio in Older Adults. (3rd April 2022) - Kakazu, Viviane Akemi; Pinto, Rafael Zambelli; Dokkedal-Silva, Vinicius; Fernandes, Guilherme Luiz; Gobbi, Cynthia; Andersen, Monica Levy; Tufik, Sergio; Pires, Gabriel Natan; Morelhão, Priscila Kalil
Abstract: Introduction: Sleep quality and weight are inversely correlated in young adults (i.e., as weight increases, sleep quality decreases), but results are still inconsistent among older adults. Objective: To examine the association between body mass index (BMI) and the waist-to-hip ratio (WHR) with sleep quality in older adults. Method: 513 participants >60 years old were recruited. Data on BMI, WHR, age, gender, alcohol consumption, depression, comorbidities, and sleep (Epworth Sleepiness Scale (ESS) and Pittsburgh Sleep Quality Index (PSQI)) were collected. Univariate and multivariate linear regression methods were used to evaluate the association between BMI, WHR and PSQI. Results: 503 participants were included. There was a significant association between BMI ( β  = 0.10 95%CI: 0.04 to 0.15) and PSQI in the linear analysis, but not confirmed in the multivariate regression. No significant associations were observed between WHR and PSQI. Conclusion: Neither BMI nor WHR were related to sleep quality in the older population.